Decreasing displacements of prestressed suspension bridge - Goremikins, Vadims; Rocens, Karlis; Serdjuks, Dmitrijs (Journal of Civil Engineering and Management, 2012)
A suspension bridge is the most suitable type for a long-span bridge due to rational use of structural materials. Increased deformability, which is conditioned by the appearance of the elastic and kinematic displacements, is the major disadvantage of suspension bridges. The problem of increased kinematic displacements under the action of symmetrical and non-symmetrical load can be solved by the prestressing. A prestressed suspension bridge with span of 200 m was considered as an object of investigations. The cable truss with the cross web was considered as the main load carrying structure of prestressed suspension bridges and was compared with the single cable. The considered prestressed suspension bridge was investigated by the FEM program ANSYS 12 and by the small scale physical model. Rational, from the point of view of minimal vertical kinematic displacements, main load-carrying structure of prestressed suspension bridge was developed. The obtained results shows, that usage of cable truss with the cross web as the main load carrying structures of prestressed suspension bridge in comparison with the single cable, reduces vertical displacements upwards by 63.1%, downwards by 1.8% and total displacements by 29.6% under the action of worth situated load.